2004
DOI: 10.1007/s00011-004-1271-3
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of IL-1 and TNF-? on proinflammatory cytokine and matrix metalloproteinase expression in human chondrosarcoma cells

Abstract: IL-1 and TNF-alpha each activate a distinct set of genes in chondrosarcoma cells, and gene expression in these cells is regulated by groups of genes related in part by their function. Chondrocyte IL-1alpha appears to serve an important role in the pathogenesis OA contributing to joint inflammation and cartilage destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 46 publications
7
49
0
Order By: Relevance
“…We and others recently reported that the pro-inflammatory cytokines interleukin-1␤ and TNF-␣ induce BMP-2 expression in adult articular chondrocytes and a chondrosarcoma cell line (12,30). Similar BMP-2 induction by those cytokines is also observed in synovial cells (14,31) and could be a widespread event in arthritic joints.…”
supporting
confidence: 60%
“…We and others recently reported that the pro-inflammatory cytokines interleukin-1␤ and TNF-␣ induce BMP-2 expression in adult articular chondrocytes and a chondrosarcoma cell line (12,30). Similar BMP-2 induction by those cytokines is also observed in synovial cells (14,31) and could be a widespread event in arthritic joints.…”
supporting
confidence: 60%
“…39 Studies by Wei et al 40 examining the effects of IL-1␤ and IFN-␥ on organ-cultured skin biopsies reported a greater degree of overlap between these two cytokines than that observed here. However, only seven proteins were analyzed by semiquantitative immunohistochemistry in the former study, with lower thresholds required for significance.…”
Section: Discussionmentioning
confidence: 43%
“…AR has been shown to be an autocrine factor in keratinocytes, so it is possible that AR-stimulated EGFR is driving this IL-1/NF-nB feedback loop in the same way as we show in SUM149 breast cancer cells (66). Sustained increases in IL-1 and NF-nB have the ability to alter matrix metalloproteinase activity and the production of other proangiogenic and invasion-inducing factors like IL-6 and IL-8 (40,52,67). Accordingly, an active autocrine loop involving IL-1, EGFR, and NF-nB would have the power to induce the rapid growth, invasion, and angiogenesis seen in aggressive breast cancer.…”
Section: Discussionsupporting
confidence: 55%